Alexander Dugin's views of Russian history: collapse and revival. (2nd September 2017) - Shlapentokh, Dmitry
Abstract: Alexander Dugin is one of the most well-known and clearly the most prolific philosopher and public intellectual in post-Soviet Russia. He was especially popular in the late 1990s and early 2000s, when he clearly had obvious political ambitions. His influence declined later on. However, he continued to be an important intellectual who clearly earned his visible place in Russian intellectual history. His ideas still reflect the opinions of a considerable segment of the Russian elite and general public. This is one of the reasons why his views, including those on Russian history, its meaning and dynamics deserve to be presented. In addition, his view of Russian history as a cycle of decline and rebirth had much more broad appeal and application. It could be traced in the cultures of many societies, especially those in crisis. Here, the theory of decline and revival provided the hope that nothing is lost and that the country could reemerge in the future even greater than it was before. While studying Dugin's views, one should remember that they changed over the course of time. This article deals with Dugin's views of Russian history, which he espoused from the 1990s to approximately the early 2000s.